Mucous patch on the tongue as isolated manifestation of the secondary stage of syphilis: Case report - Bjekić Milan; Šipetić Sandra (Serbian Medical Society - Dental Section, Belgrade, 2012)
Introduction. Syphilis is sexually transmitted infection caused by the anaerobic spirochete Treponema pallidum. Oral lesions are present and described in all stages of the disease. These lesions as well as blood and saliva of infected persons are highly contagious in early syphilis. The aim of this case report was to point out to the possibility of the secondary syphilis in differential diagnosis of oral diseases. Case Report. A 38-year-old asymptomatic man showed up at the clinic with suspicious of syphilis infection. Clinical presentation of the disease was a mucous patch on the tongue, however no other mucous membrane or cutaneous lesions were detected. No lymph nodes were enlarged. The serologic tests on syphilis were positive. After conducting systemic antibiotic therapy with benzathine penicillin the tongue lesion disappeared. Conclusion. Depending on the clinical picture, the possibility of syphilis should not be overlooked in the differential diagnosis of oral lesions.